Hybrid inorganic/organic microstructured light-emitting diodes produced using photocurable polymer blends - Sun, Handong (2009)
Light-emitting diodes LEDs in the form of a one-dimensional array of microstripes emitting at 370 nm were fabricated from AlInGaN inorganic semiconductor. These microlight sources were then used to “directly write” microstructures in photocurable blends of organic light-emitting